EFEKTIFITAS PENGGUNAAN BUKU AJAR STATISTIK DALAM MENINGKATKAN HASIL BELAJAR MAHASISWA - Amirulmukminin Amirulmukminin; Ita Purnama (Program Studi PGSD Universitas Flores, 2023)
At the beginning of 2020, the world was shaken by a deadly virus attack, namely, Covid 19. As a result, all activities were completely paralyzed, including teaching and learning activities. Seeing these conditions, the researchers compiled a statistics textbook as a guide for STIE Bima students. For this reason, the purpose of this study was to look at the effectiveness of using statistics textbooks in improving student learning outcomes in semester II of STIE Bima in the 2021/2022 Academic Year. Thus, lecturers will be able to compile teaching books by taking into account the characteristics and needs of students. This research involved 80 students who were divided into 2 classes. This research is a development research. Before the Statistics Textbook is distributed to students, validity is first tested. From the results of the two statistics textbook validators are in the valid criteria, that is, minor improvements were made such as the use of language, typing errors and others. The results of the analysis, it was found that the use of statistical textbooks had a high effectiveness in increasing student learning outcomes, this was indicated by the N-Gain value of 0.71 greater than or equal to 0.7 with an N-Gain percentage value of 70.54%. Not only that, it can also be seen in the increase in the average score in the pre-test versus post-test by 65.79%.